Zum Wandel der öffentlichen Verwaltung in den liberalisierten Netzwerkindustrien - Michael W. Bauer (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2002)
– Transformation Towards a new Public Administration of the Network UtilitiesDuring the 1980s and 1990s privatisation and deregulation movements have been shaken up the European network industries-telecommunication, electricity and railways. These reforms did affect also those parts of the public administrations in charge of managing and controlling the industries. While usually the changes in the relationship 'administration-market' have been the centre of academic attention, this paper attempts to investigate whether the very functions of the public administration themselves have been affected, i.e. altered or even transformed. Goes the emergence of the regulatory state hand in hand with the arrival of a new public administration? Comparing the examples of regulatory reform in the United Kingdom and Germany this paper attempts to provide a first answer.
Keywords: 330; Verwaltungsreform; Telekommunikationspolitik; Elektrizitätspolitik; Eisenbahnpolitik; Deregulierung; Großbritannien; Deutschland